2019
DOI: 10.3389/fnins.2019.01302
|View full text |Cite
|
Sign up to set email alerts
|

How Cognition and Motivation “Freeze” the Motor Behavior in Parkinson’s Disease

Abstract: ObjectiveFreezing of gait (FoG) is a debilitating problem in patients with PD. The multifactorial pathogenesis of FoG remains poorly understood. We aimed to find which factors are most strongly associated with the occurrence of FoG.MethodsThree hundred five PD patients were enrolled and subdivided according to the presence (FoG +, n = 128) or absence (FoG-, n = 177) of FoG. Several clinical, functional, and neuropsychological data were collected and compared between groups. The association between the probabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 88 publications
(111 reference statements)
1
14
0
3
Order By: Relevance
“…We found FOG in PD to be unrelated to sex and only weakly associated with patient age, consistent with the majority of other prospective studies [ 4 , 8 , 10 12 , 30 ]. On the other hand, supporting extensive literature, we found disease duration to be strongly associated with FOG [ 4 7 , 9 , 12 , 13 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found FOG in PD to be unrelated to sex and only weakly associated with patient age, consistent with the majority of other prospective studies [ 4 , 8 , 10 12 , 30 ]. On the other hand, supporting extensive literature, we found disease duration to be strongly associated with FOG [ 4 7 , 9 , 12 , 13 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Levodopa equivalent dose was strongly correlated with motor complications ( p < 0.0001), supporting previous studies showing a strong relationship between levodopa dose and development of both wearing-off symptoms and dyskinesias [ 39 ], and was also confirmed as a significant independent risk factor for FOG in our logistic regression analysis. Levodopa dose has previously been linked to FOG in PD [ 7 , 8 , 10 ] and, in at least one study, was also shown to exert an effect on FOG independent from that of motor complications [ 8 ]. In our study, participants with motor complications who had a higher LED (≥750 mg) had more frequent freezing (67% versus 33%, p =0.009) but similar severity of freezing relative to those receiving a lower LED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive decline, especially in executive functions, has been associated with gait disorders and risk of falling. 16 , 20 The association between executive functions and bradykinesia has been reported in individuals with PD, 3 , 18 as well as the correlation between the ability to divide attention between two tasks and balance. 30 …”
Section: Discussionmentioning
confidence: 94%
“… 19 Executive function deficit, mainly inhibitory control and mental flexibility, has been associated with gait impairment and freezing of gait (FOG). 11 , 20 , 21 Another study revealed that gait and balance are related to specific cognitive skills, suggesting similar cerebral cortical circuitry for mobility and cognitive function. 13 …”
Section: Introductionmentioning
confidence: 99%